2020
DOI: 10.21203/rs.3.rs-29072/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research Training Program in a Turkish Medical School: Challenges, Barriers and Opportunities from the Perspectives of the Students and Faculty Members

Abstract: Background: Providing medical students with opportunities for research experience is challenging for medical schools in developing countries. The Research Training Program (RTP), which is carried out in Ege University Faculty of Medicine (EUFM) parallel to the core curriculum, aims to improve the scientific competencies of the highly motivated students and to provide them with the opportunity to conduct a research. The purpose of this project is to evaluate RTP through the perspectives of students and faculty … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies suggest that students who had been exposed to research during the entire curriculum showed much more interest in research at a post graduate level and improved the ratio of biomedical researchers. [18][19][20] Although student-led research is increasing gradually, the ratio of overall physician scientists has been decreasing and quality research needs to be emphasized. 21 Our study also showed that 50% of the students scored more than 60% overall in the assessments, reflecting that attention should be paid towards strengthening research teaching at undergraduate level in order to have better researchers at the postgraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that students who had been exposed to research during the entire curriculum showed much more interest in research at a post graduate level and improved the ratio of biomedical researchers. [18][19][20] Although student-led research is increasing gradually, the ratio of overall physician scientists has been decreasing and quality research needs to be emphasized. 21 Our study also showed that 50% of the students scored more than 60% overall in the assessments, reflecting that attention should be paid towards strengthening research teaching at undergraduate level in order to have better researchers at the postgraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that potential benefits, including academic promotion obtained through working with students should be clearly explained to supervisors. 42 Furthermore, securing a pool of supervisors ready to work with students is paramount for supporting student research. 43 Lack 44,45 It has been suggested that providing a built-in research training component within the curriculum seems to be a more realistic goal, 11 and has already been implemented in several settings including Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…During the residency period, mentor should transfer his/her experience in this field, provide guidance at every step, and help with establishing a professional network ( 25 ). Residency students should be assigned an active role in every step of research such as guiding to project, preparing a project, and time management, and this can be achieved via mentorship ( 26 ). Moreover, another problem is the insufficiency of the mentors ( 21 , 25 ).…”
Section: Discussionmentioning
confidence: 99%